Early T-Cell Precursor Acute Lymphoblastic Leukemia: Diagnosis, Updates in Molecular Pathogenesis, Management, and Novel Therapies - Sin, Chun-fung; Man, Pui-hei Marcus (Frontiers in Oncology, 2021)
Early T-cell precursor acute lymphoblastic leukaemia (ETP-ALL) is a distinct subtype of T lymphoblastic leukaemia (T-ALL) identified in 2009, due to its unique immunophenotypic and genomic profile. The outcome of patients was poor in earlier studies and they were prone to have induction failure, with more frequent relapse/refractory disease. Recent advances had been made in discoveries of genetic aberrations and molecular pathogenesis of ETP-ALL. However, the diagnosis and management of ETP-ALL is still challenging. There are limited choices of novel therapies so far. In this review article, it highlighted the diagnostic issue of ETP-ALL, pitfall in diagnosis and strategy of accurate diagnosis. The review also summarized current understanding of molecular mechanism of leukemogenesis. The emerging role of risk-adapted therapy and allogenic stem cell transplant in optimizing the outcome of patients with ETP-ALL was discussed. Finally, some potential novel therapies were proposed based on the current understanding of molecular pathogenesis.